ANALISIS FAKTOR-FAKTOR MEMPENGARUHI MINAT BELI KONSUMEN ONLINE PADA USAHA PEMPEK KOTA JAMBI - Dini Elida Putri (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2022)
The importance role of Small and Medium Enterprise (SME) in the economics sector is undeniable and marketing management implemented for SME’s development in the future ahead and factually sees there is a need in modern society for culinary tourism. In Jambi city, one of the local cuisine product is called Pempek, which is a kind of food made from fish and processed into types of variant. Some of small shops that sell pempek in Jambi city had implemented marketing mix strategy in their business and used digital technology as a media for their online business promotion. The purpose of this research is to analyze the influence of marketing mix on online consumers buying interest (willingness to buy) of pempek product in Jambi city and to analyze level of marketing mix simultaneously influence online consumers buying interest (willingness to buy) of pempek product in Jambi city. This research is quantitative research. Instrument used in a form of Likert scale questionnaire. The research population is consumers of pempek in Jambi city, for online buyers and the sample decided for this research is 100 respondent, with purposive sampling technique. Software SPSS V.23 is used to analyze data collection.The result shows that “price” is a factor which had a significant and positive effect on consumers buying interest / willingness to buy, with significance level 0,000 < 0,05. In F test result shows Fcount>Ftable (167,219 > 2,70), with Adjusted R Square is 0,870, means that independent variable (marketing mix) has 87% influencing dependent variable (buying interest).